Re-conceptualizing Nepal’s Security Policies: A Comprehensive Framework for Addressing Non-Traditional Security Threats (The Shivapuri Journal, 2025)
Nepal’s security setting is changing due to the rise of non-traditional security threats (NTSTs),  including climate change, cybersecurity  risks, transnational crimes,  public health crises, and environmental degradation.  However,  Nepal’s current security policies remain predominantly state-centric, focusing on traditional military and political concerns, while failing to adequately address the complexities of emerging non-traditional threats.  This paper critically examines the policy gaps, institutional weaknesses, and legal shortcomings in Nepal’s security framework.  The study explores how Nepal can re-conceptualize its security policies by    adopting a    comprehensive, multi-dimensional, and proactive security framework using a theoretical and analytical approach. This research identifies major challenges in Nepal’s security governance, including fragmented policies, weak institutional coordination, outdated legal frameworks, inadequate regional cooperation, and low public engagement through an extensive literature review and policy analysis. The study proposes a holistic security model,  integrating strategic policy reforms, institutional strengthening, legal advancements, regional cooperation, and public participation to enhance Nepal’s resilience against non-traditional security threats.  The findings suggest that without urgent reforms,  Nepal will remain vulnerable to emerging threats that undermine its social, economic, and environmental stability. The paper concludes with strategic recommendations for policymakers, emphasizing the  importance of an integrated, forward looking, and human-centric security approach to safeguard Nepal’s national interests in the 21st century.